Conservation of coastal marine environments - West, Robert C. (Revista de Biología Tropical, 1976)
The intertidal zones of the Central American coasts are here classified as 1) cliffed or rocky headlands, 2) sandy beaches and 3) low-lying alluvial coasts. The ecosystems associated with these zones are among the most complex and biologically productive, but least understood, of the biosphere. Emphasis is placed on the importance of estuarine alluvial coasts with tidal, or mangrove, forests, which comprise approximately 30 percent of the Central American coastline. As demonstrated by studies in southern Florida, estuarine mangroves play a key role in the maintenance of juvenile forms of marine life by controlling the availability of nutrients through the accumulation of decaying detritus and the growth of organisms on the stilt roots. Thus the preservation of mangrove is essential for the maintenance of much of the offshore fishing resources. But in various parts of the Central American coast, mangrove is endangered by overcutting, industrial pollution, and urban resort development. Although less vulnerable than the mangrove coast, sand beaches and cliffed headlands deserve conservational consideration because of both their biologic and touristic value. The establishment of national parks and wildlife refuges along various parts of the Central American littoral may be a first step in the conservation of that region's coastal resources.